Behavior and failure mechanisms of masonry-infilled RC frames (in low-rise buildings) subject to lateral loading - Basha, Syed Humayun; Kaushik, Hemant B. (Engineering structures, 2016)
•Shear design provision for masonry infilled RC frames are experimentally evaluated.•Results showed inadequacy of current standards in preventing columns shear failure.•Stiffening action provided by the RC slab resulted in only minor damage in beams.•Three performance levels are proposed for design of masonry infilled RC frames. The behavior of eleven half-scale, single-story masonry infilled reinforced concrete (RC) frames under slow cyclic in-plane lateral loading was experimentally studied in two stages. Results obtained in the first stage (eight frames) showed that the frames infilled with full-scale and half-scale bricks exhibited higher strength, stiffness, and energy dissipation than their bare frame counterparts. In most cases, columns failed in shear even though the masonry used was quite weak. In order to delay the shear failure in columns, shear design of columns was enhanced as per the existing earthquake standards, and tests were repeated on three improved frames in the second stage. Though shear failure in columns of the improved frames occurred at higher drift level, the shear failure in columns could not be prevented showing the inadequacy of current design codes. Based on the experimental results, an idealized load–displacement relationship for masonry infilled RC frames was developed for different performance levels.